Industrial Relations Today: Reining in Flexibility - Streeck, Wolfgang (Economics, Management & Financial Markets, 2009)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with "flexibility" and "flexicurity." It recalls the dissolution of the "Fordist" compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy.
Keywords: corporate growth; countermovement; industrial relations; international economic relations; labor laws & legislation; labour laws & legislation; socioeconomics; welfare economics

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Keywords: commodification; commodification of nature